2008
DOI: 10.1073/pnas.0804632105
|View full text |Cite
|
Sign up to set email alerts
|

Demyelination arrest and remyelination induced by glatiramer acetate treatment of experimental autoimmune encephalomyelitis

Abstract: The interplay between demyelination and remyelination is critical in the progress of multiple sclerosis (MS) and its animal model, experimental autoimmune encephalomyelitis (EAE). In the present study, we explored the capacity of glatiramer acetate (GA, Copaxone) to affect the demyelination process and/or lead to remyelination in mice inflicted by chronic EAE, using both scanning electron microscopy and immunohistological methods. Spinal cords of untreated EAE mice revealed substantial demyelination accompanie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
75
0
4

Year Published

2010
2010
2014
2014

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 108 publications
(85 citation statements)
references
References 20 publications
6
75
0
4
Order By: Relevance
“…It inhibits Th17 and Th1 responses (54) and boosts CD4 + CD25 + regulatory T cells in the EAE model (16). It also promotes several other beneficial effects in the inflamed CNS, such as remyelination, oligodendrogenesis (32,55), neuroaxonal protection, and neurogenesis (56)(57)(58). Previous gene-expression studies in PBMCs obtained from untreated versus GA-treated MS patients showed that GA reduced the expression of proinflammatory cytokines, such as TNF (59).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It inhibits Th17 and Th1 responses (54) and boosts CD4 + CD25 + regulatory T cells in the EAE model (16). It also promotes several other beneficial effects in the inflamed CNS, such as remyelination, oligodendrogenesis (32,55), neuroaxonal protection, and neurogenesis (56)(57)(58). Previous gene-expression studies in PBMCs obtained from untreated versus GA-treated MS patients showed that GA reduced the expression of proinflammatory cytokines, such as TNF (59).…”
Section: Discussionmentioning
confidence: 99%
“…To investigate whether the gene panel could be useful for evaluating the effectiveness of experimental therapies, we measured differential expression of the selected genes during development of MOG-induced EAE in mice that had been treated prophylactically with GA. We chose to use GA because it is effective in ameliorating MOG-induced EAE in both prophylactic and therapeutic protocols, shows protective properties in CNS tissues (32), and is an established drug for the treatment of MS (33). Most mice treated prophylactically with GA by s.c. injection every 7 d, starting from 7 d preimmunization with MOG, showed reduced disease incidence, delayed onset, and significantly milder clinical scores compared with those in the nontreated group (Fig.…”
Section: Differential Expression Of Marker Genes Precedes Lesion Devementioning
confidence: 99%
“…On the one hand, lovastatin (HMG-CoA reductase inhibitor) [40] , glamorgan acetate [41] , guanosine or guanine [42] , ciliary neurotrophic factor [43] , thymosin β4 [44] , and endogenous leukemia inhibitory factor [45] , through different cascades of signal transduction, increase the numbers of NG2 cells and oligodendrocytes, and put an end to the demyelination process. The expression of platelet-derived growth factor α receptors (PDGFαRs) increases during the proliferation of NG2 cells, and NG2 proteoglycan expression disappears as NG2 cells differentiate into mature oligodendrocytes [46] .…”
Section: Remyelination In Multiple Sclerosis (Ms): Ng2 Cells Functionmentioning
confidence: 99%
“…Early animal studies on the neuroprotective effects of GA show promise. Spinal cords of glatiramer acetate-treated EAE mice show significantly reduced demyelination and enhanced remyelination compared to controls (Aharoni et al, 2008). Moreover, when treatment was initiated at the time of manifestation of clinical symptoms, or even in the chronic disease phase when extensive demyelination had already accumulated, GA dramatically reduced pathological damage.…”
Section: Preventing Free Radical Damagementioning
confidence: 90%